Feeding of Atlantic Cod ( Gadus morhua ) at Low Temperatures - Waiwood, K. G.; Smith, S. J.; Petersen, M. R. (Canadian Journal of Fisheries and Aquatic Sciences, 1991)
Satiation level, feeding frequency and maximum meal size of Atlantic cod (Gadus morhua) fed frozen shrimp (Pandalus montagui) were determined at temperatures of 1, 4, and 8 °C. Satiation level was predicted by a statistical model which separated the occurrence of feeding from the amount ingested. Decreased consumption of food at low temperatures was found to be primarily a function of decreased feeding frequency rather than decreased meal size. On a daily basis, cod ate 87, 77, and 54% of the time on average at 8, 4, and 1 °C, respectively. The average meal size, calculated over feeding days only, was directly related to the size of the fish and not to temperature. However, the maximum meal size was smaller, particularly for the larger fish at low temperatures.